2010
DOI: 10.1016/j.alcohol.2009.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Roles of neural stem cells and adult neurogenesis in adolescent alcohol use disorders

Abstract: This review discusses the contributions of a newly considered form of plasticity, the ongoing production of new neurons from neural stem cells, or adult neurogenesis, within the context of neuropathologies that occur with excessive alcohol intake in the adolescent. Neural stem cells and adult neurogenesis are now thought to contribute to the structural integrity of the hippocampus, a limbic system region involved in learning, memory, behavioral control, and mood. In adolescents with alcohol use disorders, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
47
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 209 publications
(368 reference statements)
3
47
0
1
Order By: Relevance
“…Therefore, it is concerning that binge alcohol consumption in teenagers is on the rise, with a significant percentage (>60%) of individuals vulnerable to developing alcohol use disorders (1,2). Studies in animal models confirm that adolescence is a period of high vulnerability, with various developmental, behavioral, neuroendocrine, and pharmacological factors, as well as alcoholinduced neuroplastic and neurodegenerative outcomes, which drive the adolescent's propensity to excessively or compulsively drink alcohol in adulthood (3)(4)(5)(6)(7)(8).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, it is concerning that binge alcohol consumption in teenagers is on the rise, with a significant percentage (>60%) of individuals vulnerable to developing alcohol use disorders (1,2). Studies in animal models confirm that adolescence is a period of high vulnerability, with various developmental, behavioral, neuroendocrine, and pharmacological factors, as well as alcoholinduced neuroplastic and neurodegenerative outcomes, which drive the adolescent's propensity to excessively or compulsively drink alcohol in adulthood (3)(4)(5)(6)(7)(8).…”
mentioning
confidence: 97%
“…There is robust evidence for alcohol-induced reductions in postnatal hippocampal neurogenesis in rodent models (7), but the underlying mechanisms are still under investigation. Importantly, recent research in young, adolescent, and adult rodents supports the hypothesis that postnatal hippocampal neurogenesis may be associated with alcohol abuse and alcohol dependence (7).…”
mentioning
confidence: 99%
“…A large body of evidence now suggests that impaired adult neurogenesis in the hippocampus is associated with various mental disorders, including major depression, schizophrenia, mood, and anxiety disorders as well as addictive behaviors. Importantly, decreased adult neurogenesis correlates with reduced cognitive and affective functions, a common symptom in patients and a frequent phenotype in animal models of these diseases, and often coincides with a decrease in cell proliferation in the dentate gyrus and reduced hippocampal volume (Bremner 1999;Lie et al 2004;Reif et al 2007;Revest et al 2009;Morris et al 2010;Nixon et al 2010;Noonan et al 2010). As adult hippocampal neurogenesis is directly linked to the action of antidepressants, it has been suggested that adult neurogenesis could be a target for treatment of depression (Banasr et al 2006;Dranovsky and Hen 2006;Drew and Hen 2007;Sahay and Hen 2007).…”
Section: Adult Neurogenesis As a Potential Therapeutic Targetmentioning
confidence: 99%
“…Whether these changes represent adaptive responses to various pathophysiological conditions, part of the pathophysiology that contributes to the disease, or both, remains a key question for the field. Interestingly, for most psychiatric disorders, such as major depression, schizophrenia, anxiety disorders, and addiction, a decrease in cell proliferation within the dentate gyrus and reduced hippocampal volume have been reported, which are associated with impaired hippocampus-dependent functions, including working memory, context-dependent memory and recognition memory, and spatial pattern separation (Bremner 1999;Lie et al 2004;Reif et al 2007;Revest et al 2009;Morris et al 2010;Nixon et al 2010). For example, a significant subpopulation of patients with major depression has consistently shown reduced hippocampal volume and cognitive deficits (Sheline et al 1996;Bremner 1999;Campbell and Macqueen 2004;Savitz and Drevets 2009;Kempton et al 2011).…”
mentioning
confidence: 99%
“…Adolescent alcohol exposure has been associated with deficits in neurogenesis (Crews et al, 2006) and an increase in neurodegeneration (Nixon et al, 2010) in a number of brain regions, and may have long-term effects on behavior through these means. Synaptic pruning, one of the most prolific developmental processes occurring during this period, is likewise altered by adolescent alcohol consumption (Selemon, 2013), particularly in the glutamatergic cell populations that project from cortical to striatal regions.…”
Section: Introductionmentioning
confidence: 99%